Educación matemática crítica para el desarrollo del pensamiento crítico: una intervención didáctica desde el análisis de problemáticas del contexto a través de la IAP (2024)
This research work was born from the need to link the teaching of mathematics in the classroom with the real-life problems of the students' context, in order to give meaning to the learning process and that students can not only develop mathematical skills, but also if critical thinking. A didactic strategy framed in Critical Mathematics Education and Participatory Action Research was carried out with the participation of 26 tenth grade students from a school in Bogota. As a result, the students critically analyzed their context, chose a problem, understood it through basic statistical analysis and applied various informative campaigns that generated a transformation in their environment.